Methodology for thermal desorption treatment of local soil pollution by oil products at the facilities of the mineral resource industry - Mariya A. Pashkevich; Marina V. Bykova (Записки Горного института, 2022)
The analysis of the main environmental consequences of leaks and local spills of petroleum products at the enterprises of the mineral resource complex is presented. It is established that the problem of soil contamination with petroleum products at the facilities of the mineral resource complex and enterprises of other industries is caused by significant volumes of consumption of the main types of oil products. Based on the results of the author's previous field research, a series of experiments was carried out, consisting in modeling artificial soil pollution with petroleum products such as gasoline, diesel fuel, highly refined oil, motor oil, and transmission oil, followed by their purification by heat treatment at temperatures of 150, 200, and 250 °C. The 250 °C limit of the heating temperature was set due to the need to partially preserve the structure and quality of the soil after heat treatment to preserve its fertility. When the processing temperature rises to 450 °C, all humates are completely burned out and, as a result, productivity is lost. Confirmation is provided by the results of experiments to determine the humus content in uncontaminated soil and soil treated at different temperatures. It was found that at a maximum processing temperature of 250 °C, about 50 % of the initial organic carbon content is preserved. According to the results of the conducted experimental studies, the dependences of the required processing temperature on the concentration of petroleum products to reduce the concentration of petroleum products to an acceptable level have been established. The methodology of thermal desorption cleaning of soils with varying degrees of contamination at enterprises of the mineral resource complex is presented.